EFEKTIFITAS PENGGUNAAN ASESMEN SUMATIF PADA PEMANASAN GLOBAL KELAS X SMAN 1 KOTO XI TARUSAN - Olivia, Olivia; Yuliani, Suci; Habib, M; Rahma, Hestia; Anaperta, Megasyani; Yanti, Iing Rika (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2026)
This study was motivated by the low effectiveness of summative assessment in measuring students' understanding of the Global Warming topic in Grade X at SMAN 1 Koto XI Tarusan. As a conceptual subject, this material requires an appropriate evaluation instrument. This research employed a quantitative method by analyzing the difficulty level, discriminating power, and reliability of 20 multiple-choice questions and 5 essay questions. The results showed that most objective items were classified as easy with low discriminating power, while the essay items were of moderate difficulty, had very good discriminating power, and high reliability. These findings indicate that essay questions are more effective in assessing students’ critical thinking skills and conceptual understanding. Therefore, developing high-quality assessment instruments is essential to improve the quality of learning.